Monitoring of train-induced vibrations on rock slopes - Jiangbo Xu; Changgen Yan; Xu Zhao; Ke Du; Heng Li; Yongli Xie (International Journal of Distributed Sensor Networks)
Train-induced vibrations will undoubtedly influence the stability of slopes near railway lines. To monitor the effects of such vibrations on slope stability, a wirelessly networked vibration test system was established, which included wirelessly networked vibration meters, high-precision and high-speed three-dimensional sensors and a remote wirelessly networked data server system. This system represents the first attempt to monitor the effects of train-induced vibrations on the stability of slopes in China. It enables real-time and long-distance monitoring by means of remote transmission with a low cost and high efficiency. The duration, frequency, amplitude, peak acceleration and peak particle velocity were adopted as measures for evaluating the influence of train vibrations. Simultaneously, we used additional monitoring technologies to verify the conclusions of the wirelessly networked vibration test system. The monitoring results indicated that the peak particle velocity was much higher near the track and gradually decreased with increasing distance. When the distance between the measurement point and the road axis was 12 m ( H  = 0 m), the maximal peak particle velocity was 0.4 mm/s, which remained below the maximum safe value.